IMPROVING STUDENT’S SPEAKING ABILITY THROUGH MOBILE SOCIAL NETWORKING: A Pre-Experimental Research - Al Fauzan , Muh. Saefullah; Syam, Ummi Khaerati; Daddi, Herlina (FKIP Unismuh Makassar, 2018)
This research aimed at finding out whether or not the implementation mobile social networking method improve the students’ ability in speaking term of accuracy and fluency at the tenth grade students’ of SMAN 8 Makassar. This research was conducted through pre-experimental method. The population of this research consisted of one class of the tenth grade and the sample of the research, the researcher took X-MIPA 1 class, which consisted of 31 students at High School SMAN 8 Makassar, year 2018/2019. In collecting data, the researcher gave a speaking test; the speaking test help into two steps, there were pre-test and post-test. The findings of this research showed that the mean score in pre-test in term of pronunciation was (3.06) and post-test was (5.65). The mean score in pre-test in term smoothness was (3.39) and post-test was (5.74). In addition, the total result of pronunciation and smoothness or X1 was (3.22) and the post-test or X2 was (5.7). So, this is showed students got improvement in their speaking after being taught through mobile social networking